Comparison of the Four-step Basic Life Support Approach with Non-Standardised Training Approach in Achieving Basic Life Support Proficiency among the Healthcare Workers - Siddiqi, Fuad Ahmad; Anwar, Wasif; Saeed, Bilal; Hussain, Maryam; Abbas, Naveed; Khan, Junaid Sarfraz (Pakistan Armed Forces Medical Journal, 2023)
Objective: To quantify the effectiveness of non-structured training versus a structured 4-step approach for basic life support (BLS) knowledge and skills using quantitative assessment tools. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Medicine, Combined Military Hospital, Peshawar Pakistan from Oct 2022 to Mar 2023. Methodology: Two hundred (n=200) healthcare workers from all Hospital Departments were included in the study through convenient sampling. They were divided into “Group-A” and “Group-B” of equal size. Group-A received BLS training through a four-step approach, whereas Group-B received non-structured teacher-based training. Pre and post-training MCQs judged the knowledge gained, and a checklist was used to assess the effectiveness of the BLS skills. Results: Both the groups had similar scores in the Pre-training test (p 0.692). Both groups improved their scores after their respective training (p<0.001 for both groups). However, Group-A got a better score (mean score =70.50±11.22) than Group- B (mean score =59.60±11.88) with a highly significant difference (p-value<0.001). There was also a significant improvement (p<0.001) in BLS skills performance as per the checklist in Group-A (mean 7.69±1.47) versus Group-B (mean 6.18±1.34) out of a maximum score of 10. Conclusion: The 4-step program is significantly better than non-standardised training in achieving BLS learning outcomes.